Compartmental Modelling in chemical engineering: A critical review. (31st December 2019) - Jourdan, Nicolas; Neveux, Thibaut; Potier, Olivier; Kanniche, Mohamed; Wicks, Jim; Nopens, Ingmar; Rehman, Usman; Le Moullec, Yann
Graphical abstract: Highlights: Compartmental modelling, a suitable method to simulate and model complex systems in chemical engineering. More precise than systemic models and less time consuming than fully reactive CFD. Synthesis and analysis of the different approaches used in compartmental modelling. Proposition of a unifying definition and step-by-step construction method. Exploration of perspectives and future challenges of compartmental modelling. Abstract: Compartmental modelling is a hybrid way to model complex systems in Chemical Engineering. This modelling approach offers numerous advantages because it aggregates information from both local and system scale models. Compartmental models allow multi-scale modelling with low computational time compared to a full coupled model (e.g. reactive numerical simulations). Thanks to these main characteristics, compartmental models are able to model complex full-size industrial systems. For the last decades, various approaches of compartmental models were developed for different applications. In this article, a critical review and analyses are carried out to classify these different approaches. A unified definition is proposed, and important guidelines are pointed out to assist with constructing a Compartmental Model. Finally, some perspectives for the future of Compartmental Modelling are identified and discussed: compartmental modelling for larger and more complex systems, the inclusion of new phenomena modelling and automation of compartmental models with the improvement of numerical methods.